1999
DOI: 10.3758/bf03211406
|View full text |Cite
|
Sign up to set email alerts
|

How to drastically reduce priming in word stem completion—and still present the words

Abstract: This paper describes a series of experiments in which we demonstrated that "dysphonemic" word stems, which are likely not pronounced in isolation as they are within a word (e.g.,MUS in MUSHROOM or LEG in LEGEND), showed less priming than did "phonemic stems" (e.g., MUS in MUSTARD or LEG in LEGACY). Furthermore, words with either dysphonemic or phonemic three-letter stems gave rise to equivalent levels of priming when test cues were four-letter stems (LEGE) or word fragments (L_G_ND). Moreover, the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…It entailed removing potential word-specific differences between auditory study and visual study and between auditory test and visual test. This second measure was in keeping with the observation of Brooks and colleagues (Brooks, Gibson, Friedman, & Yesavage, 1999) that word-specific factors may be more potent determinants of long-term priming than are conventional manipulations (e.g., modality and processing task at study). Of particular concern for stem (and fragment) completion tasks is the phonological consistency of the words selected for the experiment.…”
supporting
confidence: 59%
See 2 more Smart Citations
“…It entailed removing potential word-specific differences between auditory study and visual study and between auditory test and visual test. This second measure was in keeping with the observation of Brooks and colleagues (Brooks, Gibson, Friedman, & Yesavage, 1999) that word-specific factors may be more potent determinants of long-term priming than are conventional manipulations (e.g., modality and processing task at study). Of particular concern for stem (and fragment) completion tasks is the phonological consistency of the words selected for the experiment.…”
supporting
confidence: 59%
“…Other experiments point to the same conclusion (e.g., Brooks et al, 1999;Rueckl & Mathew, 1999). Of significance to this suggested revision-and of relevance to identifying the phonology in question-are observations that phonetic length affects visual lexical decision.…”
Section: The General System For Learning and Identifying Wordsmentioning
confidence: 62%
See 1 more Smart Citation
“…Thus, both Backman et al (1997) and Daselaar et al (2005) examined the effects of aging on word-stem completion priming, a test that appears to rely not only on perceptual processes, but also on conceptual and phonemic processes (Brooks, Gibson, Friedman, and Yesavage, 1999; Rueckl and Mathew, 1999). Backman et al (1997) reported no age difference in priming and similar RS for young and elder subjects in extrastriate cortex.…”
mentioning
confidence: 99%
“…However, against other published rates from North American samples, we can show a good match. Comparing rates for lists published in Brooks, Gibson, Friedman, and Yesavage (1999), our database produces mean rates for each list (where stems overlap) that are different only by an average of 1.9%. This suggests at least some utility for non-British samples.…”
Section: Supplemental Materialsmentioning
confidence: 99%